Urban Agglomeration and COVID-19 Clusters: Strategies for Pandemic Free City Management - Manawadu, L.; Gunathilaka, K.L.W.I.; Wijeratne, V.P.I.S. (International Journal of Scientific and Research Publications, 2020)
Cities become central locations that coordinate most of the socio economic networks of a country. Therefore the urban agglomerations that have high population densities are identified as the most vulnerable hotspots during a period of pandemic in a country. Therefore this study focuses mainly on the identification of sustainable strategies for pandemic free city management in developing countries in a post COVID era. Literature related to the context along with the scholarly articles were reviewed in fact collection in this study while using diagrams and flow charts in information presentation. The study could investigate the urban agglomerations of developing countries as the most vulnerable sites for the clustering of COVID 19 cases in the world. Further the underserved settlements, public service places, manufacturing industries, retail service centers, transportation hubs, banking and finance sections, educational institutions and health care centers were identified as the clustering hot spots of infection carriers in more than 85% of the developing countries. Thus the study concluded that the practical measures should be implemented by deviating from prevailing liberalized policies and major urbanization characteristics like human interactions and movements while strengthening and monitoring the prevailing social distancing and health precautions for a better achievement in almost all the socio economic sectors of the country in the reawakening after a period of two month quarantine until the discovery of a reliable cure for the pandemic.
Keywords: COVID 19, urban agglomeration, Developing countries, COVID 19 hotspots